The sources of ethical decision making for individuals in the public sector. - Van Wart, Montgomery (Public Administration Review)
The American Society for Public Administration recently streamlined and considerably amended its code of ethics to make it more useful for practitioners and to align it to literature on public sector ethics. The new code reduces 12 categories of unequal significance into five overarching principles: public interest, legal interest, personal interest, organizational interest, and professional interest. At a basic level, the code forbids grossly unethical behavior, and at a more sophisticated level, it acknowledges that the really difficult administrative decisions are those that involve two or more legitimate value sources competing for attention. The code is much more than a list of legalistic prohibitions; it is a powerful tool for decision analysis and an aspirational call for excellence in the profession.